Coordinate high-frequency pattern of stimulation and calcium levels control the induction of LTP in striatal cholinergic interneurons - Bonsi, Paola (Cold Spring Harbor Laboratory Press, 2004)
Current evidence appoints a central role to cholinergic interneurons in modulating striatal function. Recently, a long-term potentiation (LTP) of synaptic transmission has been reported to occur in these neurons. The relationship between the pattern of cortico/thalamostriatal fibers stimulation, the consequent changes in the intracellular calcium concentration ([Ca(2+)](i)), and the induction of synaptic plasticity was investigated in striatal cholinergic interneurons from a rat corticostriatal slice preparation by means of combined electrophysiological intracellular recordings and microfluorometric techniques. Different protocols of stimulation were considered, varying both the frequency and the duration of the train of stimuli. High-frequency stimulation (HFS) (three trains at 100 Hz for 3 sec, 20-sec interval) induced a rise in [Ca(2+)](i), exceeding by fivefold the resting level, and caused a LTP of synaptic transmission. Tetanic stimulation delivered at lower frequencies (5-30 Hz) failed to induce long-term changes of synaptic efficacy. The observed elevation in [Ca(2+)](i) during HFS was primarily mediated by L-type high-voltage activated (HVA)-Ca(2+) channels, as it was fully prevented by nifedipine. Conversely, blockade of NMDA and AMPA glutamate receptor did not affect either LTP or the magnitude of the [Ca(2+)](i) rise. Interestingly, the pharmacological analysis of the post-tetanic depolarizing postsynaptic potential (DPSP) revealed that LTP was attributable, to a large extent, to the potentiation of the GABA(A)-mediated component. In conclusion, the expression of LTP in striatal cholinergic interneurons is a selective response to a precise stimulation pattern of induction requiring a critical rise in [Ca(2+)](i).